Optimisation of the Danish national haemoglobinopathy screening programme – A prospective intervention study - Esther Agnethe Ejskjær Gravholt; Finn Stener Jørgensen; Charlotte Holm; Jesper Petersen; Amina Nardo‐Marino; Mathis Mottelson; Andreas Glenthøj (eJHaem)
Abstract Introduction The Danish national haemoglobinopathy screening programme offers screening to at‐risk pregnant women. Despite efforts to increase awareness of the screening programme, most women in the target population remain unscreened. In contrast, > 90% of pregnant women in Denmark attend a screening for chromosomal abnormalities by combined first‐trimester screening (cFTS). Methods This study aimed to improve adherence to the Danish national haemoglobinopathy screening programme by offering screening to at‐risk unscreened pregnant women in relation to their cFTS. Results During a 27‐week intervention period, 3254 women attended cFTS at Copenhagen University Hospital—Amager Hvidovre Hospital. Of these, 938 women (28.8%) were identified as at risk of carrying haemoglobinopathy variants based on their ethnic origins. Of the 938 women at risk, 539 (57.5%) were unscreened prior to their cFTS and were targeted for the intervention. These women were contacted with an offer of haemoglobinopathy screening. Subsequently, 253/539 (46.9%) of the at‐risk unscreened women were tested for haemoglobinopathies, of these 4/253 (1.6%) carried haemoglobinopathy variants necessitating partner screening. No partners carried haemoglobinopathy variants necessitating testing of the fetus. Conclusion The study increased the proportion of at‐risk pregnant women tested for haemoglobinopathies from 42.5% to 69.5% and made haemoglobinopathy screening more readily available to women attending cFTS.